SOUTH ASIA DYNAMICS AFTER THE TALIBAN OVERTHREW ASHRAF GHANI’S REGIME IN AFGHANISTAN 2021 - Afriandi, Edo; Saragih, Hendra Maujana (Journal of Social Political Sciences, 2022)
Afghanistan itself is known to be experiencing an internal conflict against the Taliban group which at this time, the country was successfully conquered by the group. This study aims to be able to understand and also conduct an analysis related to the process of transition of power in Afghanistan which was previously held by President Ashraf Ghani then shifted under the rule of the Taliaban. In this study, the author uses two theories, namely the theory of the transfer of power and the theory of regional security. To support the results of a more comprehensive research the author uses a qualitative approach research method. The results of this study explain that the government held by Ashraf Ghani is very weak, so that after the withdrawal of troops from the United States and Nato, the country experienced a government vacuum so that it was used by the Taliban to dominate areas in Afghanistan including Kabul which is the capital of the country. Besides that, there are also dynamics that occur in the South Asian region by looking at some of the responses given by the countries in the region related to the stability of the Security in the South Asian region.